Regeneração natural de Apuleia leiocarpa (Vogel) J.F. Macbr. em floresta manejada no estado do acre - Domingos Neto, Victor Carlos (2017)
In view of the difficulty of establishing the natural regeneration of Apuleia leiocarpa in areas of natural forest without anthropic impact, it was decided to investigate the conditions that favor and limit its development, with a view to the vulnerability of this species in different typologies forest in which it occurs. For this reason, we evaluated a forest area after two years of logging in the southwest of the Brazilian Amazon, located in the municipality of Porto Acre, state of Acre. The population of A. leiocarpa was characterized based on data from forest inventory pre-exploratory and, for better understanding of the behavior of the species in the area, the species were grouped in diametric class as the formula proposed by Sturges. The analysis of the spatial pattern of the species in the area was evaluated using the function K to Ripley, even at a distance of 500 meters, corresponding to half the lower side of the area. For evaluation and determination of factors influence and limiting factors in its development, we selected trees seed port with dbh greater than 80 cm and with crowns, remnants of forest management and distributed in two different situations: areas that have not been damaged the activities of forest management and areas with damage caused by logging. For the evaluation of natural regeneration, from the regrowth, were selected tree stumps, exploited in a random manner, distributed throughout the UPA with the objective of sampling different situations postexploratory. The remaining individuals from logging with dbh greater than 30 cm have diametric distribution uneven, with the largest number of individuals in the intermediate classes and are distributed spatially aggregated form. The mechanisms of regeneration of the species Apuleia leiocarpa found were the plants originating in the dispersal of seeds and regrowth of vegetative parts by means of differentiation. The regenerantes of seminal origin are dependent on opening of clearings and scarification of the soil to develop, they were distributed in classes of height with an exponential negative and maximum height of two meters. The development of the regrowth at two years of age was superior to that of origin, with heights of up to eight meters and circumference at 10 cm from the base up to 15 cm, demonstrating an efficient mechanism of regeneration of the species.